Tatlong taong walang Diyos? - Aunor, Nora; De Leon, Christopher; Roco, Bembol,t; O'Hara, Mario (1976)
A woman falls in love with a Japanese soldier during the Japanese Occupation in the Philippines; the whole town turns against her.